Victorian Voting: The Origins of Party Orientation and Class Alignment. Issue 4 (21st November 2019) - Dewan, Torun; Meriläinen, Jaakko; Tukiainen, Janne
Abstract: Much of what we know about the alignment of voters with parties comes from mass surveys of the electorate in the postwar period or from aggregate electoral data. Using individual elector‐level panel data from nineteenth‐century United Kingdom poll books, we reassess the development of a party centered electorate. We show that (a) the electorate was party‐centered by the time of the extension of the franchise in 1867, (b) a decline in candidate‐centered voting is largely attributable to changes in the behavior of the working class, and (c) the enfranchised working class aligned with the Liberal left. This early alignment of the working class with the left cannot entirely be explained by a decrease in vote buying. The evidence suggests instead that the alignment was based on the programmatic appeal of the Liberals. We argue that these facts can plausibly explain the subsequent development of the party system.